Analisis Pengaruh Harga, Kualitas Produk dan Iklan Terhadap Pengambilan Keputusan Pembelian Konsumen Pada Pasar Modern (Studi Kasus Carrefour Solo Baru) - Rianto, Agus; , Ir. Irmawati, SE, Msi (2017)
The purposes of this research are to know whether the variables of price, product quality and advertisement have an influence on the consumers' purchase decision in the Modern Market (a case study of Carrefour Solo Baru) partially and to know which variabe is the most dominant in the consumers' purchase decision process. The research method used in this research is survey using the method of sampling through the technique of purposive sampling. Samples in this research are 100 respondents. Type of the data is primary data. The method of data collection used the quistionnaire.The technique of data analysis used is the multiple linear regression. The results of instrument test showed that all are valid and reliable. The multiple linear regression showed that together, variables X1,X2,X3 showed a positive influence on variable Y. The results of t test revealed that there is an influence partially between the independent variable and the dependent variable. The result of f test showed that there is a collective influence among variables. The result of coefficient determination or R2 revealed that the ability of independent variable can descrobe the dependent variable. The rest is influenced by other variables which are excluded in the model.